The exceptional VHE gamma-ray outburst of PKS 1510-089 in May 2016 - Michael Zacharias; Julian Sitarek; Dijana Dominis Prester; Felix Jankowsky; Elina Lindfors; Mahmoud Mohamed; David Sanchez; Tomislav Terzic (Italy, 2025)
PKS 1510-089 (z=0.361) is one of only a handful of flat spectrum radio quasars that have been detected at very high energy (VHE, E > 100GeV) gamma rays. It is a very active source across the entire electromagnetic spectrum. VHE observations in May 2016 with H.E.S.S. and MAGIC revealed an exceptionally strong flare, which lasted for less than two nights, and exhibited a peak flux of about 0.8 times the flux of the Crab Nebula above 200GeV. The flare provides the first evidence of intranight variability at VHE in this source. While optical observations with ATOM reveal a counterpart at optical frequencies, Fermi-LAT observations reveal only low flux variability at high energy (HE, E > 100 MeV) gamma rays. Interestingly, the HE spectral index significantly hardens during the peak of the VHE flare, indicating a strong shift of the peak frequency of the high energy component. Given the expected strong absorption due to the broad-line region, the VHE emission region cannot be located deep within that region.
35th International Cosmic Ray Conference, ICRC 2017